Quantifying wintertime boundary layer ozone production from frequent profile measurements in the Uinta Basin, UT, oil and gas region. Issue 18 (19th September 2016) - Schnell, Russell C.; Johnson, Bryan J.; Oltmans, Samuel J.; Cullis, Patrick; Sterling, Chance; Hall, Emrys; Jordan, Allen; Helmig, Detlev; Petron, Gabrielle; Ahmadov, Ravan; Wendell, James; Albee, Robert; et al.
Abstract: As part of the Uinta Basin Winter Ozone Study, January–February 2013, we conducted 937 tethered balloon‐borne ozone vertical and temperature profiles from three sites in the Uinta Basin, Utah (UB). Emissions from oil and gas operations combined with snow cover were favorable for producing high ozone‐mixing ratios in the surface layer during stagnant and cold‐pool episodes. The highly resolved profiles documented the development of approximately week‐long ozone production episodes building from regional backgrounds of ~40 ppbv to >165 ppbv within a shallow cold pool up to 200 m in depth. Beginning in midmorning, ozone‐mixing ratios increased uniformly through the cold pool layer at rates of 5–12 ppbv/h. During ozone events, there was a strong diurnal cycle with each succeeding day accumulating 4–8 ppbv greater than the previous day. The top of the elevated ozone production layer was nearly uniform in altitude across the UB independent of topography. Above the ozone production layer, mixing ratios decreased with height to ~ 400 m above ground level where they approached regional background levels. Rapid clean‐out of ozone‐rich air occurred within a day when frontal systems brought in fresh air. Solar heating and basin topography led to a diurnal flow pattern in which daytime upslope winds distributed ozone precursors and ozone in the Basin. NO x ‐rich plumes from a coal‐fired power plant in the eastern sector of the Basin did not appear to mix down into the cold pool during this field study. Key Points: Wintertime ozone formation in a gas field Shallow, rapid photochemical ozone